Physical and optical properties of zinc oxide micro and nanostructures deposited on various substrates - Kamalianfar, Ahmad (2014)
This thesis attempts to investigate some unknown properties of ZnO microand nanostructures as one of the most promising materials in this decade. Additionally, the interaction between the components consisting of ZnO,buffer layers and substrates can produce new physical properties which may provide some important utilization in electronic and optoelectronic devices. The aim of this work is to study the effect of various substrates with metal or metal oxide layers including Au, Ag, Cu and Au+Cu alloy on the structural,morphological and optical properties of ZnO micro- and nanostructures. In addition, the relevant growth mechanisms are also proposed. The experiments are carried out in a quartz tube using a vapor phase transport of a carbon-zinc oxide mixture at different temperatures (900-1000˚C). The main thesis work involves six distinct studies. Firstly, the conditions to grow ZnO micro- and nanostructures deposited on various substrates such as Si, GaN and corning glass without metal buffer layers are studied and optimum conditions for each morphology are identified. The results indicate that a gas pressure in range of 70 and 90 standard cubic centimeters per minute and 15 cm distance between the source and substrates are necessary for formation of nanostructures with diameters less than 100 nm. ZnO microsphere structure with a radius of around 1.5 μm was obtained under 80 standard cubic centimeters per minute (sccm) gas pressure rate and 30 cm distance from the source. The multipods composed of nanowires and nanorods have been grown on different distributions of Ag nanoparticles on silicon substrates. A low distribution of Ag particles on the substates results in formation of multipod structure with pods ranged from 50-100 nm in diameter, and several micrometers in length. The diameters of the pods are increased (400 nm- 500 nm) while the substrate with more concentration of Ag particles is used. ZnO flower-like multisheets were grown on silicon and corning glass substrates with Cu and Cu+Au alloy buffer layers. Comparison with the clean silicon substrate, the PL spectrum of the flower grown on the Cu/Si shows a higher intensity UV emission peak and the lower intensity visible emission peak. The spectrum also exhibits a higher intensity of the visible emission for ZnO crystalline on the Au+Cu/Si and Cu/Si than the ZnO grown on Si substrate. Shift of the E2 mode in Raman spectrum indicates that the nanowires or nanosheets grown on metal buffer layers are under more in-plane stress. ZnO peach-like morphology was grown on MgO (111) substrate with copper oxide buffer. The sizes of the peaches are not uniform and the diameters of the peaches are ranged from 2 to 5 micrometers. The photoluminescence spectrum demonstrates a strong peak in the ultraviolet (UV) region at around 380 nm, originated from the exciton related recombination. The peak positions at 495 and 520 nm can be assigned to oxygen and zinc vacancies, respectively. The high intensity of E2 (high) mode in the Raman spectrum indicates a good crystallization of the prepared sample. Two different quartz tubes were used to study the effect of different vapor super-saturation on the samples. The XRD patterns have indicated that the crystalline quality of the samples grown using one closed end tube was better than those with both opened ends. Based on the field emission scanning electron microscope images, larger ZnO nanostructures were obtained from one closed end tube due to the O2-rich atmosphere.